Influence of lifestyle factors-sleep patterns and stress on skin health and ageing amongst the general population in India - K. R., Vishal; Anuhya, Katta; Imran, Sarmad; Khanduja, Sneha; Yeshasri, Chennagouni (International Journal Of Community Medicine And Public Health, 2024)
Background: This study examines the impact of lifestyle factors, particularly sleep patterns and stress, on skin health and aging in the Indian population. The findings provide valuable information for health professionals, policy makers and individuals to develop targeted interventions and recommendations to promote healthy skin and combat premature aging. Methods: The study utilized SPSS Software (by IBM) for descriptive and inferential statistical tests, calculating frequencies and percentages of categorical variables. Descriptive statistics summarized participants’ characteristics, while the chi-square test was used to investigate associations between socio demographic factors and acne. The total of 510 participants was included in the analysis. Results: To investigate categorical factors associated with skin finding (acne), Chi-square test was used to find the association and where the expected count in cells was less than 5, Fisher Exact test was applied. Statistical significance determined at p<0.05. There was a total of 510 individuals but 7 did not consent to participate so 503 individuals were included in analysis. Conclusions: The use of smartphones has had a big impact on sleep patterns, which are crucial for preserving physiological balance. Sleep disturbances can cause dryness and irritation of skin. A diet high in fruits and vegetables like tomatoes, red grapes are directly linked to promoting skin health. Blue light exposure from smartphones and other electronics can cause hyperpigmentation, premature wrinkles, tanning, and other skin problems. Nomophobia is a phenomenon that we see in this age of reliance on technology, especially cell phones.